TATA KELOLA SI AKADEMIK BERBASIS COBIT 2019 UNTUK PENINGKATAN KUALITAS INFORMASI DI SMK AL AMIN - Amrullah; Baiq Yulia Fitriyani (Jurnal Manajemen Informatika dan Sistem Informasi, 2026)
Academic information quality plays a strategic role in supporting decision-making processes and enhancing the effectiveness of educational management in schools. However, in practice, many schools continue to experience challenges related to the accuracy, consistency, and reliability of academic information due to information system governance and management that have not yet been optimally implemented. This study aims to assess the current condition of academic information system governance and management while formulating an improvement model based on the COBIT 2019 framework to enhance academic information quality in schools.This research adopts a quantitative approach using an evaluative method. Data were collected through literature review, field observations, interviews, and questionnaires developed according to selected COBIT 2019 domains, namely EDM02 (Ensure Benefits Delivery), EDM04 (Ensure Resource Optimization), EDM05 (Ensure Stakeholder Engagement), and APO14 (Manage Data). The collected data were analyzed to determine process maturity levels, identify existing gaps, and formulate improvement recommendations.The results indicate that the maturity level of academic information system governance and management falls within the defined process to established process categories, with maturity scores ranging from 60.1% to 70%. The primary gaps were identified in academic data management, optimization of information technology resources, and the measurement of information system benefits. Based on these findings, this study recommends strengthening academic information system governance and management through improved data management practices, optimal utilization of IT resources, and enhanced stakeholder involvement. The proposed model is expected to serve as a reference for schools in sustainably improving academic information quality